MASTITIS PATHOGENS AND THEIR ANTIMICROBIAL SUSCEPTIBILITY IN EARLY LACTATING DAIRY COWS - TRAJCHEV, Metodija; NAKOV, Dimitar; PETROVSKA, Milena; JANKOSKA, Gordana (Journal Agriculture and Forestry, 2017)
A two years cross-sectional longitudinal survey was carried out for determination of udder pathogens prevalence and their antimicrobial profile in one commercial dairy farm. Dairy cows were selected in relation to date of calving and period of early lactation in order to minimize environmental impact. A udder quarters milk samples were obtained from totally 211 black-white dairy cows. The quarter milk-samples were screening using the California Mastitis Test (CMT) for detection of abnormal milk secretion (AMS) and from quarters with AMS were obtained milk-samples for microbiological examination in order to detect intramammary infections (IMI). The milk-samples were obtained in two periods: period from beginning of lactation until 21st day in lactation and period from 22nd to 42nd day in lactation. The prevalence of IMI in period from beginning of lactation until 21st day in lactation and period from 22nd to 42nd day in lactation was 4.03% and 4.38%, respectively. Based on CMT, there was found totally 162 udder quarters with AMS. From these quarters, the overall proportion of microbiological negative quarters was 56.17% and mastitis pathogens were isolated from 43.83% of udder quarters, from which the dominant mastitis pathogens were: Streptococcus agalactiae (19.14%), Enterococcus spp. (8.02%), Candida non-albicans (6.79%), Staphylococcus aureus (6.17%), Escherichia coli (1.85%), Aspergilus niger (1.23%) and Pseudomonas aeruginosa (0.62%). The results indicated that contagious pathogens were the most common patogens of IMI in early lactation. There was significant difference in the prevalence of intramammary infection (χ2=35.136, df=1, p<0.001) when comparing the front and rear udder quarters. The isolated bacteria were examined for determination of susceptibility to 27 most used antimicrobial agents for mastitis treatment. The most resistant strain was Staphylococcus aureus.
Keywords: dairy cow, intramammary infection, lactation